2021
DOI: 10.1177/1077801221998786
|View full text |Cite
|
Sign up to set email alerts
|

“There’s Girls Who Can Fight, and There’s Girls Who Are Innocent”: Gendered Safekeeping as Virtue Maintenance Work

Abstract: Women routinely practise taxing safety strategies in public, such as avoiding unlit spaces after dark. To date, scholars have understood these behaviors as means by which women bolster their physical safety in public. My in-depth interviews with women in Greater Vancouver, British Columbia suggest that, much less than reliably enhancing women’s safety, safety work often exacerbates women’s fear of violent crime and unreliably mitigates their exposure to violence. I thus interrogate the protective function of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Researchers have reported that often women still do not realize that violence in a relationship is considered abuse (Cervantes & Sherman, 2021). In the same manner, many women fear being victimized by strangers, although the likelihood is much lower than victimization by known people (Lennox, 2021; Linder & Lacy, 2020). Previous experience of being in an abusive relationship was not related to Likelihood scores for women in either country on two items.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported that often women still do not realize that violence in a relationship is considered abuse (Cervantes & Sherman, 2021). In the same manner, many women fear being victimized by strangers, although the likelihood is much lower than victimization by known people (Lennox, 2021; Linder & Lacy, 2020). Previous experience of being in an abusive relationship was not related to Likelihood scores for women in either country on two items.…”
Section: Discussionmentioning
confidence: 99%
“…Ademais, a associação cultural da iluminação como sinônimo de modernidade e progresso pode causar sentimentos de retrocesso e de "descuido" por conta da redução da iluminação noturna, visto que prover iluminação de qualidade é uma obrigação do Estado. A atenção na iluminação pública deve considerar ainda questões interseccionais, como a percepção de segurança no espaço público por grupos minorizados 6 como mulheres (Green et al, 2015;Lennox, 2022;Parra-Medina;Messias, 2011). Para haver consenso entre sustentabilidade e bem-estar, Green et al (2015) defendem a boa comunicação.…”
Section: Sustentabilidade O Acesso à Iluminação E As Diferentes Demandasunclassified
“…Alguns ambientes terapêuticos precisam de uma iluminação ainda mais flexível para o bem-estar dos usuários. Villela e Ely (2020, 2022 analisam espaços de Práticas Integrativas e Complementares (PIC) 9 e indicam que a simplicidade na estética dos ambientes e nos estímulos lumínicos influencia no bem-estar e contribui ao processo terapêutico do paciente. "Entretanto, sua percepção negativa também pode ocorrer, quando denotam 'impessoalidade', 'despersonalização' e 'frieza'" Ely, 2022Ely, , p. 2019.…”
Section: A Iluminação No Cuidado Da Saúdeunclassified
“…In performing gender (Butler, 1990; West & Zimmerman, 1987), risk avoidance through safekeeping can be a strategy used by some women to perform an identity that is culturally read as “appropriate” femininity. Historically, women were thought to be protecting a desired femininity based on being “virtuous” or “prudent” (Cops & Pleysier, 2011; Lennox, 2022; Stanko, 1997) and “mitigating the threat of social judgment, blame, and lost access to resources that men's violence threatens” (Lennox, 2022, p. 656). Central to women's internalization of risk and performance of safekeeping is the threat posed by a “dangerous male ‘other’” (Stanko, 1997, p. 488)—similar to how some scholars argue that prison staff perceive and navigate risk in relation to the “dangerous other” prisoner (Drake, 2011).…”
Section: Gender and Safekeepingmentioning
confidence: 99%